1964
DOI: 10.1139/v64-312
|View full text |Cite
|
Sign up to set email alerts
|

THE RELATIVE EASE OF REDUCTIVE CLEAVAGE OF 1,3-DIOXOLANES AND 1,3-DIOXANES IN ETHER SOLUTION BY LiAlH4–AlCl3

Abstract: In ether solution, 1,3-diosolanes are hydrogenolyzed faster by LiAII-Id-AlCl3 than are the corresponding 1,3-dioxanes. This difference is attributed to the relative ease of oxocarbonium ion formation in the rate-determining step of the reaction. The results obtained have been utilized to explain the selective cleavage of the five-and six-membered acetal structures found in the polyacetals of hexitols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1968
1968
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…104 > 105 Information about the splitting of (C 2 H 5 ) 2 O by lithium tetrahydroaluminate is not available.…”
Section: Solubility and Complex Formationmentioning
confidence: 99%
“…104 > 105 Information about the splitting of (C 2 H 5 ) 2 O by lithium tetrahydroaluminate is not available.…”
Section: Solubility and Complex Formationmentioning
confidence: 99%
“…The technique was also valuable in the investigation of the transformations of secondary and tertiary amines to C-and iV-alkyltetrahydropyrazoles effected by radiation (Carbowax 1000 column 389 ) and in the study of cleavage of dioxolanes by action of various agents. 386 By means of GLC the reversibility of the scission of 2-methyldioxolane-l,3 [15] by acetyl chloride was revealed 337 : CH2CH2OCOCH3 0CHCICH3 Diastereoisomeric 1,3-dioxolane derivatives formed by the reaction of (db) camphor and optically active 2,3-butanediol were successfully resolved by GLC at 125°C on a 6-m column of firebrick coated by 20% tri(cyanoethoxy)propane. Optical rotation of camphor isomers after hydrolysis of ketals corresponded to material of 76.5-77.5% optical purity.…”
Section: Heterocycles With Two or More Heteroatomsmentioning
confidence: 99%
“…65 The application of GLC to such compounds is hence complicated by additional difficulties. (Table XX) GLC was successfully applied to thiadiazolidine-5-ones, 383 pyrazolines, 384 oxazolines, 212b thiazoles, 385 oxadiazoles, 204 phenyl-substituted iV-phenylpyrazols, 165 1,3-borazoles, 190 purines, 202 and substituted 1,3-dioxolanes, 386 ' 387 including isomeric ketals [13] and [14] formed from ( ± ) camphor and D-f-)-butanediol-2,3, 388 Chromosorb W, 383 Celite 545, 384 Embacel, 190 Gas-Chrom P, 387 and sodium chloride 387 were among the conventional supports used, without preliminary alkali treatment. The instability of pyrazolines rendered it necessary to use glass columns, a magnetic glazed syringe, a glass vaporizer, and Teflon union joints.…”
Section: Heterocycles With Two or More Heteroatomsmentioning
confidence: 99%
“…7,8 This reaction was then thoroughly explored by Brown et al, who showed that 1,3-dioxolane were more reactive than 1,3-dioxane rings and that 2-phenyl substituents considerably accelerate the reaction. 9, 10 Gorin were the first to apply it in carbohydrate chemistry, 11 while the Liptaḱ group further demonstrated the 4-OBn/6-OH regioselectivity of the LiAlH 4 /AlCl 3 -promoted reaction on 3-O-benzyl-4,6-O-benzylidenehexopyranosides. 12 Searching for more chemoselective conditions for the reductive opening of benzylidene, Garegg et al identified the NaBH 3 CN/HCl system, previously introduced by Horne and Jordan, 13 and demonstrated its ability to chemoselectively reduce benzylidene acetals in the presence of O-benzoyl or N-acetyl moieties.…”
Section: ■ Introductionmentioning
confidence: 99%